Non-Pharmacological Intervention for Memory Decline - Cotelli, Maria; Manenti, Rosa; Zanetti, orazio; Miniussi, Carlo (Frontiers in Human Neuroscience, 2012)
Non-pharmacological treatment of memory difficulties in healthy older adults, as well as those with brain damage and neurodegenerative disorders, has gained much attention in recent years (Ball et al., 2002, Willis et al., 2006, Acevedo and Loewenstein, 2007). The two main reasons that explain this growing interest in memory rehabilitation are the limited efficacy of current drug therapies and the plasticity of the human central nervous system (Cotelli et al., 2011c) and the discovery that during aging, the connections in the brain are not fixed but retain the capacity to change with learning. Moreover, several studies have reported enhanced cognitive performance in patients with neurological disease, following non-invasive brain stimulation (i.e., repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) to specific cortical areas). The present review provides an overview of memory rehabilitation in individuals with Mild Cognitive Impairment (MCI) and in patients with Alzheimer’s Disease (AD) with particular regard to cognitive rehabilitation interventions focused on memory and non-invasive brain stimulation. Reviewed data suggest that in patients with memory deficits, memory intervention therapy could lead to performance improvements in memory, nevertheless further studies need to be conducted in order to establish the real value of this approach.